High performance epoxy-based composites for cryogenic use: A approach based on synergetic strengthening effects of epoxy grafted polyurethane and MWCNTs-NH2. (10th November 2019) - Jia, Liying; Qi, Pengfei; Shi, Ke; Liu, Xin; Ma, Wenli; Lin, Song; Zhang, Fei; Jia, Xiaolong; Cai, Qing; Yang, Xiaoping
Abstract: Synergetic strengthening effects of epoxy grafted polyurethane (EP-PU) and aminated MWCNTs (MWCNTs-NH2 ) on mechanical performance of EP-based composites at 77 K were systematically investigated using the tested results at room temperature (RT) as comparisons. EP-PU was successfully synthesized by controlling the reaction between –OH in EP and –NCO in PU prepolymer, which showed the advantages of relatively low viscosity and outstanding chemical miscibility with EP matrix. The most obvious enhancements were achieved with contents of 30 wt% EP-PU and 0.2 wt% MWCNTs-NH2 in tensile, flexural, impact and KIC fracture toughness properties of EP composites as well as flexural properties and interlaminar shear strength (ILSS) of carbon fiber (CF)/EP composites at both RT and 77 K, which confirmed the synergetic strengthening effects of EP-PU and MWCNTs-NH2 . Specifically, KIC fracture toughness of EP composites and ILSS of CF/EP composites at 77 K were enhanced by 26.0 and 31.4%, respectively, compared with the corresponding neat composites. The EP-PU component showed β or γ relaxation behavior at cryogenic condition and existed in form of scattered micro-spheres in cured EP matrix due to the phase separation. The riveting and bridging of MWCNTs-NH2 around EP-PU micro-spheres were considered to provide extraordinary synergy on the effective stress diversion and crack propagation inhibition at cryogenic condition through establishing the chemically bonded multi-scale interface.